2006
DOI: 10.1111/j.1365-3024.2006.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia surface protein (WSP) inhibits apoptosis in human neutrophils

Abstract: Polymorphonuclear cells (PMNs) are essential for the innate immune response against invading bacteria. At the same time, modulation of PMNs' apoptosis or cell death by bacteria has emerged as a mechanism of pathogenesis. Wolbachia bacteria are Gram-negative endosymbionts of filarial nematodes and arthropods, phylogenetically related to the genera Anaplasma, Ehrlichia and Neorickettsia (family Anaplasmataceae). Although several pathogens are known to interfere with apoptosis, there is only limited information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 26 publications
1
44
0
3
Order By: Relevance
“…Brattig and colleagues reported that recombinant WSP activates dendritic cells and macrophages through TLR2 (6), and we reported that WSP is readily detected in the cornea after injection of microfilariae (16). Moreover, WSP induces IL-8 production in canine peripheral blood neutrophils (5) and also inhibits apoptosis of human neutrophils (4). Future studies will examine the role of WSP and other putative ligands in O. volvulus/Wolbachia-induced keratitis.…”
Section: Vol 75 2007mentioning
confidence: 78%
“…Brattig and colleagues reported that recombinant WSP activates dendritic cells and macrophages through TLR2 (6), and we reported that WSP is readily detected in the cornea after injection of microfilariae (16). Moreover, WSP induces IL-8 production in canine peripheral blood neutrophils (5) and also inhibits apoptosis of human neutrophils (4). Future studies will examine the role of WSP and other putative ligands in O. volvulus/Wolbachia-induced keratitis.…”
Section: Vol 75 2007mentioning
confidence: 78%
“…Two other wsp genes are present in the Wolbachia genome, of which one (wspA) is usually used in strain identification and phylogeny analyses (68), although currently these analyses are completed by multilocus sequence typing (3,4,47). The wsp locus encodes an outer surface protein (Wsp) whose homologue in Wolbachia strain wDm from the nematode Dirofilaria immitis is able to inhibit the apoptosis of human granulocytes (6). A gene for an antigenic outer membrane protein, a member of the p44 multigene family, is also cotranscribed with the virB-virD4 cluster in A. phagocytophilum (43).…”
Section: Discussionmentioning
confidence: 99%
“…Together with neutrophils, the key role of macrophages in the inflammation associated with onchocerciasis and lymphatic filariasis has been demonstrated (61,421). In this respect, some studies indicated that WSP induces the chemotaxis of neutrophils (37) and can inhibit their apoptosis in vitro, which could contribute to the extension of the inflammatory state (36). Moreover, the presence of Wolbachia or of its molecules in the cytoplasm of leukocytes of dogs and humans with cardiopulmonary or subcutaneous dirofilariasis has been shown by immunohistochemistry (162, 216) (see Fig.…”
Section: Immunopathogenic Mechanisms In Dirofilariasismentioning
confidence: 99%